A multi-scale based cohesive zone model for the analysis of thickness scaling effect in fiber bridging. (8th February 2017) - Canal, Luis P.; Alfano, Marco; Botsis, John
Abstract: A cohesive zone model (CZM) is proposed to assess the thickness scaling effect associated with fiber bridging during fracture. The CZM was developed through a multi-scale simulation approach and utilizes an embedded cell model of the Double Cantilever Beam (DCB) that explicitly accounts for the bridging bundles on the fracture plane. In particular, micromechanical simulations of failure were carried out, for varying arms thickness, in order to determine the homogenized fracture behavior. To model the observed scaling effect, the conventional cohesive law, formulated as an opening-stress relation, is enriched with information on the crack opening angle. Continuum finite element simulations indicated that the proposed CZM was able to mimic very well the essential features observed in the experiments, e . g . raising R-curve behavior and thickness scaling effect on the energy dissipated at steady state.